1993
DOI: 10.1161/01.cir.88.2.562
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cigarette smoking on human autonomic function.

Abstract: In habitual smokers, smoking acutely reduces baseline levels of vagal-cardiac nerve activity and completely resets vagally mediated arterial baroreceptor-cardiac reflex responses. Smoking also reduces muscle sympathetic nerve activity but augments increases of sympathetic activity triggered by brief arterial pressure reductions. This pattern of autonomic changes is likely to influence smokers' responses to acute arterial pressure reductions importantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
3
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 50 publications
8
102
3
2
Order By: Relevance
“…Life-style factors have been reported to affect cardiovascular autonomic function [25,26]. In our study only weak and less consistent associations were observed.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Life-style factors have been reported to affect cardiovascular autonomic function [25,26]. In our study only weak and less consistent associations were observed.…”
Section: Discussioncontrasting
confidence: 86%
“…Besides diabetes, many other factors possibly influence the outcome of cardiovascular autonomic function tests, including age [13±15], sex [16], anthropometric factors [17], cardiovascular disease [18,19], use of anti-hypertensive drugs [20,21], metabolic factors [22±24], and lifestyle [25,26]. Since most of these associations have been described in persons without diabetes, it is not known to what extent such factors contribute to the severity of autonomic dysfunction in diabetic subjects.…”
mentioning
confidence: 99%
“…Enhancement of ghrelin secretion could also be an indirect influence mediated by other factors, including growth hormone (nicotine increases the growth hormone concentration) (9 ), leptin (inverse correlation with ghrelin concentrations) (10 ), and vagal nerve stimulation (smoking affects vagal nerve activity) (11 ). Our finding that smoking is more likely to produce an acute release of intracellular ghrelin into the circulation rather than a time-or dose-dependent stomach secretion is partially in agreement with the hypothesis of investigators (4,5 ) that circulating ghrelin concentrations are related to the time elapsed after smoking.…”
Section: Smoking Acutely Increases Plasma Ghrelin Concentrationsmentioning
confidence: 99%
“…Bilirubinemia influencing front-face ZnPPIX determinations depends on the instrument (7,8), use of intact vs lysed specimens (9 ), or washing of intact cells before use (10 ). Although jaundice can be present in malarial disease, bilirubinemia is loosely correlated with disease severity (11 ). Asymptomatic parasitemic children are likely to have lower concentrations and incidence of hyperbilirubinemia.…”
Section: To the Editormentioning
confidence: 99%
“…A large body of literature (reviewed in Kalman, 2002) points to nicotine being a source of subjective pleasure, or positive hedonic impact. Nicotine also elicits an increase in sympathetic arousal (Niedermaier et al, 1993). The classical conditioning model therefore predicts that airway sensory stimulation will elicit both positive hedonic impact and sympathetic arousal.…”
mentioning
confidence: 99%